FORMATION OF VALUABLE-SENSITIVE BASES OF THE PEDAGOGICAL PROFESSION IN THE UNIVERSITY - Bugaychuk, Tatyana; Khodyrev, Aleksandr; Когiakovtseva Olga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The authors of the article present a study of the features of the value-semantic bases of the activity of students of a pedagogical university of 1 - 5 courses, describe the dynamics of the phenomenon studied during the training. The authors comprehend the relevance of this problem in the context of modernizing pedagogical education. Based on the leading principles of the concept of professional development of personality, the authors describe one of the components of professional identity - value, the features of the crisis of the third year and the leading terminal and instrumental values during the professional training of students in the university.